Mannitol Is Required for Stress Tolerance in Aspergillus niger Conidiospores - Ruijter, George J. G. (American Society for Microbiology, 2003)
d-Mannitol is the predominant carbon compound in conidiospores of the filamentous fungus Aspergillus niger and makes up 10 to 15% of the dry weight. A number of physiological functions have been ascribed to mannitol, including serving as a reserve carbon source, as an antioxidant, and to store reducing power. In this study, we cloned and characterized the A. niger mpdA gene, which encodes mannitol 1-phosphate dehydrogenase (MPD), the first enzyme in the mannitol biosynthesis pathway. The mpdA promoter contains putative binding sites for the development-specific transcription factors BRLA and ABAA. Furthermore, increased expression of mpdA in sporulating mycelium suggests that mannitol biosynthesis is, to a certain extent, developmentally regulated in A. niger. Inactivation of mpdA abolished mannitol biosynthesis in growing mycelium and reduced the mannitol level in conidiospores to 30% that in the wild type, indicating that MPD and mannitol 1-phosphate phosphatase form the major metabolic pathway for mannitol biosynthesis in A. niger. The viability of spores after prolonged storage and germination kinetics were normal in an mpdA null mutant, indicating that mannitol does not play an essential role as a reserve carbon source in A. niger conidia. However, conidiospores of a ΔmpdA strain were extremely sensitive to a variety of stress conditions, including high temperature, oxidative stress and, to a lesser extent, freezing and lyophilization. Since mannitol supplied in the medium during sporulation repaired this deficiency, mannitol appears to be essential for the protection of A. niger spores against cell damage under these stress conditions.